Developing evaluation standards for learning outcomes in aerobics for students majoring in physical education at Bac Ninh Sports University (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Developing evaluation standards for learning outcomes in aerobics for students majoring in physical education at Bac Ninh Sports University